Looking for truth in absurdity: Humour as community-building and dissidence against authoritarianism. Issue 5 (November 2022) - Korkut, Umut; McGarry, Aidan; Erhart, Itir; Eslen-Ziya, Hande; Jenzen, Olu
What makes humour an honest and a direct communication tool for people? How do social networking and digital media transmit user-generated political and humorous content? Our research argues that the way in which humour is deployed through digital media during protest action allows protestors to assert humanity and sincerity against dehumanising political manipulation frameworks. Humorous content, to this extent, enables and is indicative of independent thinking and creativity. It causes contemplation, confronts the hegemonic power of the oppressor, and challenges fear and apathy. In order to conduct this research, we collected and analysed tweets shared during the Gezi Park protests. Gezi Parkı was chosen as the keyword since it was an unstructured and neutral term. Among millions of visual images shared during the protests, we concentrate on those that depict humour both in photography and video formats.